Normalization Policy of Ukrainian-Polish Relations in the mid-1930s: Essence, Causes, and Preconditions - Demchyshak, Ruslan; Zavada, Yaryna (Studia Warmińskie, 2022)
The article attempts to analyse the historical event that was the process of normalisation of Ukrainian-Polish relations in the mid-1930s. It analyses the rationale that led to the conclusion of a normalisation agreement in 1935 between the Ukrainian National Democratic Union (UNDO) - the most influential social representative in the Ukrainian community in the western territories of Ukraine at the time - and the Polish government represented by representatives of the Sanation. In addition, the reasons that favoured the normalisation policy are discussed. The conclusion of the agreement was a landmark step. In exchange for a declaration of loyalty and the UNDO’s recognition of the Polish raison d’état, the government was to implement many Ukrainian demands. For the UNDO, it was an opportunity to create parliamentary representation and ensure that Ukrainian NGOs were able to function, while for the Sanation, it was a chance to gain a political ally among Ukrainians in the region and the Polish parliament. In this way, the civic equality of Ukrainians was marked. At the same time, convergence of views on many issues was emphasised, but also issues that should be resolved and put in order were pointed out.